2018
DOI: 10.2495/wm180331
|View full text |Cite
|
Sign up to set email alerts
|

Batch Reactor Pyrolysis of Stabilized Sewage Sludge: Product Analysis and Sulphur Balance

Abstract: Prior to sewage sludge application to agricultural soil, the sludge should be treated appropriately to suppress its negative features like content of microorganic pollutants or leaching heavy metals. Pyrolysis has been investigated as one way of producing sewage sludge-derived biochar (solid pyrolysis residue) which is stable and less toxic than sewage sludge. A significant amount of heat must be provided to the pyrolysis process due to its endothermic character. To make the process economically and energy eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Despite a slight increase in their content at a pyrolysis temperature of 600 • C, we may conclude that their content in the gas generally decreases when the pyrolysis temperature increases. Combined with the sulfur content in other pyrolysis products, we observed that the sulfur balance and distribution among pyrolysis products (Figure 3) is relatively independent of any pyrolysis temperature above 500 • C [25]. Therefore, the decreasing sulfur content is the result of its dilution in the increased gas volume as the S-species are mostly released from the sludge to the gas phase up to pyrolysis temperatures of 400-500 • C [26,27].…”
Section: Gas Compositionmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite a slight increase in their content at a pyrolysis temperature of 600 • C, we may conclude that their content in the gas generally decreases when the pyrolysis temperature increases. Combined with the sulfur content in other pyrolysis products, we observed that the sulfur balance and distribution among pyrolysis products (Figure 3) is relatively independent of any pyrolysis temperature above 500 • C [25]. Therefore, the decreasing sulfur content is the result of its dilution in the increased gas volume as the S-species are mostly released from the sludge to the gas phase up to pyrolysis temperatures of 400-500 • C [26,27].…”
Section: Gas Compositionmentioning
confidence: 89%
“…Sulfur-containing compounds of pyrolysis gas depending on pyrolysis temperature, Adapted from Moško et al[25].…”
mentioning
confidence: 99%